1962
DOI: 10.2136/sssaj1962.03615995002600010022x
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Physiological Response of Barley and Beans Grown in Artificially Compacted Soils

Abstract: Three soils of the Atlantic Coastal Plain were compacted into steel drums with a vibrating probe. The physiological responses of barley and snap beans to changes in soil physical properties due to compaction were measured.On Galestown sand an increase in bulk density from 1.3 to 1.6 g. per cc. resulted in a 50% increase in yield of barley which was linearly and significantly correlated with increased available water. A 37% barley yield decrease with increasing bulk density from 1.3 to 1.65 g. per cc. on Freeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

1965
1965
1986
1986

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…A significant increase in the grain yield of rice over control may be attributed to a) the increased availability of moisture by way of reducing downward percolation, b) optimum mechanimcal strength for emergence and shoot growth, c) favourable plant response to the interaction between the soil physical properties brought out by compaction. Several other workers, FLOCKER et al (1959), ROSENBERG and WILLITS (1962) have observed that plant responded well to soil compaction. The decrease in rice yield with the increase in compaction level may be attributed to increased mechanical impedence and reduced condition (low Eh) in the compacted soil.…”
Section: Methodsmentioning
confidence: 89%
“…A significant increase in the grain yield of rice over control may be attributed to a) the increased availability of moisture by way of reducing downward percolation, b) optimum mechanimcal strength for emergence and shoot growth, c) favourable plant response to the interaction between the soil physical properties brought out by compaction. Several other workers, FLOCKER et al (1959), ROSENBERG and WILLITS (1962) have observed that plant responded well to soil compaction. The decrease in rice yield with the increase in compaction level may be attributed to increased mechanical impedence and reduced condition (low Eh) in the compacted soil.…”
Section: Methodsmentioning
confidence: 89%
“…The crop responses to compaction also depend on clay contents of soils. Yields indicated large negative effects of compaction on soils with high clay contents compared with the soils low in clay contents (Rosenberg and Willits, 1962;Hakansson, 1982). This suggests that when explaining compac tion responses of a soil, its texture must be considered.…”
Section: Factors Affecting Soil Compactionmentioning
confidence: 99%
“…A compactação do solo modifica a sua densidade, pa rimetro muito utilizado para caracterizá-la (ROSENBERG £ WILL ITS, 1962;GROHMANN & QUEIROZ NETO, 1966), reduz a porcentagem de macroporos (LAWTON, 1945;GRABLE 8 SIEMER, 1968;EAVIS, 1972), reduz a condutividade hidráulica saturada (ROSENBERG & WILLITS, 1962;SILVA et alIi, 1977;BELTRAME et al1í, 1981) e afeta outros parâmetros ou pro priedades que irão influenciar o desenvolvimento radicular e, finalmente, o de toda a planta e sua produção (LOWRY et alü , 1970) . Devido a modificações de arejamento que podem oco£ rer com a compactação, alguns autores constataram altera ções em algumas características químicas, como variações no pH, teores de P disponível e de Al trocável (RUSSELL, 1963;WATTS et alü, 1973, citados por PRIMAVESI, 1980 .…”
Section: Introductionunclassified